PENGISIAN DAYA MENGGUNKAN PV UNT Rancang Bangun Sistem Pengisian Daya Menggunakan PV Untuk Smart Loker - Sunardi Sunardi; Aziz Kurniawan (CV. Multi Kreasi Media, 2022)
This study discusses the design of a Charging System using pv and Smart Lockers, lockers with double security that aims to overcome the safety problems of goods stored in public places. Smart lockers require continuous electricity flow, so Pv is used as an electricity supply for smart lockers. Discusses how to make smart lockers and the energy generated by solar panels. This study aims to find out how to design smart lockers and the energy produced by solar panels. How to make a Smart Locker using RFID and Keypad by determining the components to be used such as Arduino Uno, RFID, 4x4 Keypad, LCD, 2 Channel Relay, Selenoid Door Lock, Buzzer all components are designed and assembled on Aduino pins that have been adjusted by the wiring of each component and programmed using Arduino IDE software. And from the measurement of the energy of the solar panels, And from the measurement of the energy of solar panels it can be concluded that the voltage and current of the solar panels depend on the intensity of the sunlight that is in can be. the voltage reached its peak at 07.00 of 14.47 due to sunny weather and a decrease at 13.00 by 11.14 due to cloudy cloudy weather the highest current was at 09.00. The Monocrystalline 50 Wp solar panel is capable of charging the accu for 6 hours from a voltage of 12.41 volts to 14.55 volts to supply the load from the smart locker.